2015
DOI: 10.1007/s12601-015-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal resistant endophytic fungi isolated from Nypa fruticans in Kuching Wetland National Park

Abstract:  Heavy metal pollution is an environmental issue globally and the aim of this study was to isolate endophytic fungi from mangrove wetlands of Sarawak to assess and test their ability to grow in the presence of various heavy metals (copper (Cu), zinc (Zn), lead (Pb), and chromium (Cr)). Samples of Nypa fruticans were collected from Kuching Wetland National Park (KWNP) for subsequent endophyte isolation. Ninety-three (93) isolates were obtained and assessed and the most resistant isolates (growing at concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…According to Choo et al . (), a Pestalotiopsis sp. isolate living as an endophyte resisted at high Pb(II) concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Choo et al . (), a Pestalotiopsis sp. isolate living as an endophyte resisted at high Pb(II) concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar activity was suggested by da Silva who showed that Chaetomium aureum was able to grow at the presence of lead nitrate and to reduce free Pb, decreasing water-soluble and exchangeable lead concentrations in soil. According to Choo et al (2015), a Pestalotiopsis sp. isolate living as an endophyte resisted at high Pb(II) concentrations.…”
Section: Microbial Communities' Analysismentioning
confidence: 99%
“…Other research successfully amplified fungal DNA with annealing temperature of 40, 47 and 54 (Choo et al 2015;Kramer et al 2016;o C Krishnan et al 2016).…”
Section: Fungus Identificationmentioning
confidence: 99%
“…Pestalotiopsis sp. isolated from Nypa fruticans from wetlands of Sarawak has been identified to be able to resist heavy metal ions (Cu, Cr, Pb and Zn) up to 1000 ppm (Choo et al, 2015) which motivated our study to assess biosorptive abilities of this endophytic fungus. Members of the Pestalotiopsis have also shown potential to be used as biofuel feedstock (Sia et al, 2017) and been able to degrade polyurethane polymers (Bong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are several encapsulation techniques available for biomass including alginate, polyacrylamide, polyvinyl alcohol, polysulfone, silica gel, cellulose and glutaraldehyde (Park et al, 2010) and the present study aims to encapsulate heavy-metal resistant Pestalotiopsis sp. (Choo et al, 2015) and further investigate the efficiency of dead and live encapsulated Pestalotiopsis sp. biomass on its biosorption abilities.…”
Section: Introductionmentioning
confidence: 99%